The Role of Primary Health Facilities in Screening for Risk Factors for Chronic Kidney Disease (CKD): Literature Review Study - Trixie, Joue Abraham; Sasube, Pratika Lawrence; Maluenseng, Priska Priyanka; Boltal, Abraham Daniel; Solang, Michael Alexander (Varians Jurnal Kesehatan Masyarakat, 2024)
Chronic Kidney Disease (CKD) is a grave health issue because it is related to quality and survival. This disease has become a problem in Public Health. Primary Level Health Facilities (PLHF) are essential in overcoming this burden. Primary Level Health Facilities can carry out three prevention measures: primary-level prevention, secondary-level prevention, and tertiary-level prevention. Primary-level prevention plays a role in preventing someone from experiencing CKD, secondary-level prevention plays a role in making a diagnosis as early as possible, and tertiary-level prevention plays a role in preventing complications that might occur.